Principal Component Analysis Multidisciplinary Applications - Sanguansat, Parinya (IntechOpen, 2012)
This book is aimed at raising awareness of researchers, scientists and engineers on the benefits of Principal Component Analysis (PCA) in data analysis. In this book, the reader will find the applications of PCA in fields such as taxonomy, biology, pharmacy,finance, agriculture, ecology, health and architecture.